If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4xy + -2xz = 0 Solving 4xy + -2xz = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '2x'. 2x(2y + -1z) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(2y + -1z)' equal to zero and attempt to solve: Simplifying 2y + -1z = 0 Solving 2y + -1z = 0 Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 2y + -2y + -1z = 0 + -2y Combine like terms: 2y + -2y = 0 0 + -1z = 0 + -2y -1z = 0 + -2y Remove the zero: -1z = -2y Add 'z' to each side of the equation. -1z + z = -2y + z Combine like terms: -1z + z = 0 0 = -2y + z Simplifying 0 = -2y + z The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| 3(x-5)+2=4(x-1) | | 2lnx(1/x)-x=0 | | 1.2x-4.3=1.7 | | 2x+36=400 | | -4x+14=-10 | | 2b-9+5b=4b+6 | | -8v=1 | | y=9+19x | | 7x+x+(x+3)=39 | | 4u+2v-7v+2u+12v-5u= | | (1-w)(4w-9)=0 | | 15x^3+21x^2=0 | | 0=3+5x+x^2-x^3 | | 5.6=1.1x+1.2 | | 7tan^2x-7=0 | | Ln(x+7)=(3x-5) | | 6x+49=28x+9 | | 2(3x+4)+5x=-1 | | 9k-1=15 | | Ln(x+7)=ln(3x-5) | | (9y-2)(3y+5)= | | Log(7x)=3.5 | | E*-3x=7.1 | | 3t-4=4t+16 | | 3x+31=12x-559 | | 17y=3x-19 | | (9+9)=(8-8) | | 10x-63=11 | | 8x^2-9x+k=0 | | 7x-2x-3x+2.73=4.49 | | 3x-5=-41 | | 9p-7= |